Efeito modulador do extrato total do Paenibacillus polymyxa RNC-D em macrófagos e Leishmania (Leishmania) amazonensis in vitro - Neris, Débora Meira (2018)
Leishmaniasis is an infection caused by Leishmania gender protozoa. The treatment of the disease is generally problematic, as the drugs used on clinical practice are toxic. One of the paths in the search for new therapeutic targets is the study of endophytic microorganisms-produced substances. In this study, the Total Lyophilized Extract (TLE) of the endophytic Paenibacillus polymyxa RNC-D was used, which was isolated from the Cerrado of São Carlos, Brazil. The TLE was assessed in terms of citotoxicity, ON production and citokynes production on BALB/3T3 fibroblasts, J774A.1 macrophages, RAW 264.7 macrophages, as well as directly on promastigote and amastigote stages of Leishmania (L) amazonensis. Our results have shown that the mortality rate of 50% (EC50) of fibroblasts (BALB/3T3) was of 1,171 mg/mL and 0,956 mg/mL after 48 and 72 hours, respectively. For macrophages (J774A.1) the mortality rate of 50% took place on doses of 0,994 mg/mL and 0,945 mg/mL after 48 and 72 hours, respectively. Regarding cellular death, at the period of 24 hours, the extract induced apoptosis and necrosis from the concentration of 5mg/mL in fibroblast (BALB/3T3) and from ≈1 mg/mL in macrophage (J774A.1). The threatment with ≈1 mg/mL concentration of the ETL induced TNF-α, IFN-γ and IL-10 cytokine production at the 24 hours period. The IL-10 had its production detected up to the 48 hours period, whereas the IL-12 was detected only at this period. For the toxicity essay on L. amazonensis promastigotes, the values of EC50 obtained at the 24 and 48 hours period were of 0,624 mg/mL and 0,547 mg/mL, respectively. Regarding promastigotes death percentage, our result have shown that the 0,5 mg/mL concentration induced death of 31% at the 24 hours period and 35% at 48 hours. As for the concentration of 1mg/mL of the extract, the death percentage was of 59% and 62% at the periods of 24 and 48 hours, respectively. For the parasitary load essay, it was observed a percentage of 25% of infected cells with na average of 3 amastigotes/cell for the groups treated with 0,1; 0,5 and 1 mg/mL of the TLE at both periods. Regarding cytokine production on RAW 264.7 macrophage that were infected/treated with the extract, a significant increase of TNF-α was observed at both periods for all tested concentrations. Concerning IFN-γ cytokine, its significant production was only observed at the 48 hours period in the 1mg/mL concentration, whereas the IL-12 production was only significant in the 0,5 mg/mL at the same period. A significant decrease of IL-4 was observed in all treated groups with the TLE at the 24 hours period. The significant ON production by RAW 264.7 macrophages was observed in the groups treated with 0.5 mg/mL and 1 mg/mL of the extract on both periods of 48 and 72 hours. Due to its modulatory action of the immunological activity, it is suggested that the TLE of P. Polymyxa RNC-D is a promising target for the development of new immunotherapeutical drugs for the treatment of several diseases, including, but not limited to, leishmaniasis.